Hyphodontia dimitica and H. subefibulata spp. nov. (Schizoporaceae, Hymenochaetales) from southern China based on morphological and molecular characters - Chen, Jia-Jia; Zhou, Li-Wei; Ji, Xiao-Hong; Zaho, Chang-Lin (Phytotaxa, 2016)
Hyphodontia dimitica and H. subefibulata collected from southern China are described as new species on the basis of a combination of morphological and molecular characters. H. dimitica is characterized by its poroid hymenophore, cream to buff fresh pore surface, large pores (2–4 per mm), a dimitic hyphal structure with thick-walled generative hyphae, and ellipsoid basidiospores measured as 3.8–4.6 × 2.8–3.5 µm. Hyphodontia subefibulata is characterized by its hydnoid hymenophore, buff-yellow to dark brown spines when dry, a monomitic hyphal structure with fairly thick-walled generative hyphae, presence of cystidia, and subglobose to broadly ellipsoid basidiospores measured as 3.2–4 × 3.0–3.5 µm. Illustrations and descriptions of these two new species are provided based on the Chinese materials.